(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This article explores the collaborative efforts of nurses and physiotherapists in maximizing functional independence among patients undergoing rehabilitation. Functional independence, encompassing mobility, self-care, and daily tasks, is essential for patients recovering from illness, injury, or surgery. Nurses play a vital role in holistic patient care, assessing needs, coordinating care plans, and providing education. Physiotherapists specialize in optimizing physical function through tailored interventions and exercise programs. Effective collaboration between nurses and physiotherapists is crucial for setting goals, monitoring progress, and adjusting interventions. Empowering patients through education, support, and involvement in decision-making fosters motivation and confidence. Real-life case studies illustrate the transformative potential of interdisciplinary rehabilitation. Recognizing the complementary contributions of nurses and physiotherapists enhances patient outcomes and promotes long-term wellness.